2020
DOI: 10.1016/j.jhep.2020.04.013
|View full text |Cite
|
Sign up to set email alerts
|

Hepatitis B surface antigen seroclearance: Immune mechanisms, clinical impact, importance for drug development

Abstract: HBsAg seroclearance occurs rarely in the natural history of chronic hepatitis B (CHB) infection and is associated with improved clinical outcomes. Many factors are associated with HBsAg seroconversion, including immune and viral factors. However, the immune mechanisms associated with HBsAg seroclearance are still difficult to elucidate. HBsAg seroclearance is the ideal aim of HBV treatment. Unfortunately, this goal is rarely achieved with current treatments. Understanding the mechanisms of HBsAg loss appears t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
83
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 111 publications
(83 citation statements)
references
References 150 publications
0
83
0
Order By: Relevance
“…Therefore, new non-invasive biomarkers are needed to determine, with high precision, the stage of fibrosis to improve prognosis evaluation in patients with Chronic Hepatitis B (CHB) and C (CHC). In patients with CHB, plasma HBsAg is used as a biomarker to stratify the risk of disease progression [ 10 , 11 ]. It has been shown that HBsAg titer was negatively correlated with the stage of the fibrosis in HBeAg-positive patients [ 11 ].…”
Section: Fibrosis Progressionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, new non-invasive biomarkers are needed to determine, with high precision, the stage of fibrosis to improve prognosis evaluation in patients with Chronic Hepatitis B (CHB) and C (CHC). In patients with CHB, plasma HBsAg is used as a biomarker to stratify the risk of disease progression [ 10 , 11 ]. It has been shown that HBsAg titer was negatively correlated with the stage of the fibrosis in HBeAg-positive patients [ 11 ].…”
Section: Fibrosis Progressionmentioning
confidence: 99%
“…An HBV infectious particle, which contains HBV genome (a partly double-stranded DNA in relaxed circular form called rcDNA), interacts with the human sodium taurocholate co-transporting polypeptide receptor (hNTCP or SLC10A1), the major HBV receptor described [ 16 ]. This interaction involved the Large Hepatitis B surface antigens (L-HBsAg), one of the three HBsAg exposed at the virion surface ( Figure 1 ) [ 11 ]. Then, HBV rcDNA is release into the nucleus where it can be integrated into the human genome or repaired by different cellular mechanisms into covalently closed circular DNA (cccDNA) [ 17 , 18 ].…”
Section: Hbv Infectionmentioning
confidence: 99%
“…12 However, clearance of hepatocytes with integrated HBV DNA may be more dependent on a HBsAgspecific immune response as these hepatocytes appear capable of only producing HBsAg (and SVP) efficiently 27 and are a major source of SVP in HBeAg negative patients. 28,29 SVP constitutes the bulk of circulating HBsAg in chronic infection and appears to be involved in the functional exhaustion of HBV (including HBsAg)-specific B-cell and T-cell immune responses, [30][31][32][33] suggesting that immune targeting of hepatocytes containing integrated HBV DNA may be more efficient with efficient HBsAg clearance. GGT is not as liver-specific as ALT and AST, and its elevation is usually associated with damage to the biliary epithelium or alteration in hepatocyte function, especially in non-viral hepatitis.…”
Section: Discussionmentioning
confidence: 99%
“…As neutralization activity of the anti-viral antibodies was not tested, variability in antibody effectiveness may have contributed to the lack of correlation between anti-viral IgG and clinical outcomes [6]. The use of seroconversion as a biomarker of acquired anti-viral immunity requires determination of the antibody levels indicative of prior infection [7][8][9][10]. Serial antibody testing during the course of COVID-19 infection in 41 patients within this cohort revealed that 71% either seroconverted or demonstrated a four-fold increase in IgG-specific antibody titers, meeting the established criteria for serologic evidence of MERS-CoV infection [6].…”
Section: Humoral Response In Sars-cov Mers-cov and Sars-cov-2mentioning
confidence: 99%